2020
DOI: 10.1021/acsomega.9b04250
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approaches of Nanoceria with Magnetic, Photoluminescent, and Gas-Sensing Properties

Abstract: The modification of CeO2 with rare-earth elements opens up a wide range of applications as biomedical devices using infrared emission as well as magnetic and gas-sensing devices, once the structural, morphological, photoluminescent, magnetic, electric, and gas-sensing properties of these systems are strongly correlated to quantum electronic transitions between rare-earth f-states among defective species. Quantitative phase analysis revealed that the nanopowders are free from secondary phases and crystallize in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 104 publications
1
10
0
Order By: Relevance
“…Quite unique redox, 1,2 optical 3 and electronic properties, 4 high oxygen mobility, 5 interesting biological activity, 6 such as the ability to mimic functions of a wide variety of enzymes, 7,8 along with low cost, cerium abundance in the earth's crust (approximately as much as copper or zinc) and ease of preparation make nanoparticulate CeO 2 one of the most studied and utilized metal oxide-based nanomaterial. Due to the large number of synthetic procedures developed, the properties of engineered nanoceria particles, including surface chemical, opto-electronic, particle shape, size and size distribution, as well as behavior in biological systems and toxicity 9,10 vary significantly, which predetermines ceria applicability in very diverse areas 11,12 from industry to biomedicine.…”
Section: Introductionmentioning
confidence: 99%
“…Quite unique redox, 1,2 optical 3 and electronic properties, 4 high oxygen mobility, 5 interesting biological activity, 6 such as the ability to mimic functions of a wide variety of enzymes, 7,8 along with low cost, cerium abundance in the earth's crust (approximately as much as copper or zinc) and ease of preparation make nanoparticulate CeO 2 one of the most studied and utilized metal oxide-based nanomaterial. Due to the large number of synthetic procedures developed, the properties of engineered nanoceria particles, including surface chemical, opto-electronic, particle shape, size and size distribution, as well as behavior in biological systems and toxicity 9,10 vary significantly, which predetermines ceria applicability in very diverse areas 11,12 from industry to biomedicine.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, we can conclude that the distinct synthesis conditions (pH, temperature, and consequently pressure) reached during microwave irradiation are responsible for the creation of intrinsic defects that support the multi-functionality of the studied hybrid ceria nanostructures 76 ⁠ since their structural, morphological, photoluminescent, magnetic and electric properties are strongly correlated with the quantum electronic transitions between rare-earth f-states found in the defective species.…”
Section: Resultsmentioning
confidence: 69%
“…Reports from their study revealed that the earth-doped nanoceria shows a fast response time (5.5 s) towards CO conversion to CO 2 . [15] A point to consider when defining the application of nanoceria is its method of synthesis. Studies have demonstrated different methods for the synthesis of nanoceria for different applications.…”
Section: Introductionmentioning
confidence: 99%
“…has also shown that doping nanoceria with rare‐earth elements such as Lanthanum will help create oxygen vacancies and a decrease in Ce 3+ species on the surface of the nanoparticles, thus displaying magnetic, photoluminescent and gas sensing properties. Reports from their study revealed that the earth‐doped nanoceria shows a fast response time (5.5 s) towards CO conversion to CO 2 [15] …”
Section: Introductionmentioning
confidence: 99%